Myocardial stunning in patients with coronary artery disease before and after treatment by method of coronary artery bypass grafting (own studies) - Kundina, V.; Babkina, T. (Journal of Education, Health and Sport, 2022)
Aim of the study: Determination of quantitative radiological indicators of myocardial revascularization effectiveness in patients with coronary artery disease in the early postoperative period. Materials and methods of research: For the implementation of the clinical objectives, 62 patients with coronary artery disease, heart failure, with preserved systolic function and systolic dysfunction were examined in the early postoperative period (up to 7 days). The patients’ age ranged from 40 to 79 years, the average age of the examined was 59.6 ± 8.2 years. 35 (56%) patients had HF with LV systolic dysfunction with EF of 49% or less. 27 (44%) patients had preserved systolic function - ejection fraction greater than or equal to 50%. Results: In the group before treatment, the average value ​​of MV was 69.4% CI 95% [65.3%; 73.5%], and after treatment the value of MV was 75.0% CI 95% (70.8%; 79.3%], p = 0.0000. Percentage of RFP inclusion in the anterior wall was 69.5% CI [66.2%; 72.8%] before treatment and significantly improved to 72.3% CI [69.1%; 75.4%] after treatment (p = 0.023). Lateral wall had a parameter value of 73.9% CI [70.7%; 77.1%] before treatment and improved perfusion up to 77.2% CI [74.3%; 80.2%] (p = 0.018). Parameter values for the intraventricular septum were 64.5% CI [60.7%; 68.3%] before treatment and 69% CI [65.2%; 72.8%] after treatment (p = 0.000034) and for the inferior wall those were 54.0% CI (49.7%; 58.3%] and 61.7% CI (57.9%); 65.6%] before and after treatment respectively (p = 0.000032). Conclusion: The determination of quantitative radiological parameters proposed as a result of this study is extremely important for the early postoperative period (7-10 days) for determination of stunned myocardial reserve and late stage of patients` management (1-1.5 years) for determination of hibernation reserve and final assessment of CABG effectiveness.